2018
DOI: 10.1038/s41598-018-20485-z
|View full text |Cite
|
Sign up to set email alerts
|

Broad impact of extracellular DNA on biofilm formation by clinically isolated Methicillin-resistant and -sensitive strains of Staphylococcus aureus

Abstract: Staphylococcus aureus is a major causative agent for biofilm-associated infections. Inside biofilms, S. aureus cells are embedded in an extracellular matrix (ECM) composed of polysaccharide-intercellular adhesins (PIA), proteins, and/or extracellular DNA (eDNA). However, the importance of each component and the relationship among them in biofilms of diverse strains are largely unclear. Here, we characterised biofilms formed by 47 S. aureus clinical isolates. In most (42/47) of the strains, biofilm formation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
114
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(125 citation statements)
references
References 34 publications
9
114
2
Order By: Relevance
“…The results obtained here suggested that sanguinarine reduced the biofilm formation of S. aureus single species mainly by mediating polysaccharides and eDNA levels, while for C. albicans single species and dual species, sanguinarine inhibited biofilm formation mainly by reducing protein and polysaccharide levels. The results were in line with previous reports that showed that the main components of S. aureus biofilms are composed of extracellular polysaccharides and eDNA, while the C. albicans biofilm matrix predominantly consists of extracellular proteins (55%), polysaccharides (25%), lipids (15%), and eDNA (5%) [31,32]. In agreement, for dual culture of C. albicans and S. aureus, sanguinarine reduced biofilm formation by synchronously reducing extracellular proteins, polysaccharides, and eDNA levels in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 92%
“…The results obtained here suggested that sanguinarine reduced the biofilm formation of S. aureus single species mainly by mediating polysaccharides and eDNA levels, while for C. albicans single species and dual species, sanguinarine inhibited biofilm formation mainly by reducing protein and polysaccharide levels. The results were in line with previous reports that showed that the main components of S. aureus biofilms are composed of extracellular polysaccharides and eDNA, while the C. albicans biofilm matrix predominantly consists of extracellular proteins (55%), polysaccharides (25%), lipids (15%), and eDNA (5%) [31,32]. In agreement, for dual culture of C. albicans and S. aureus, sanguinarine reduced biofilm formation by synchronously reducing extracellular proteins, polysaccharides, and eDNA levels in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 92%
“…MR23 is a hyper-Eap-producing strain compared with other clinical isolates, as recently reported (34). In addition, the protein level of SasG in MR23 was similar to or higher than those in most other strains ( Fig.…”
supporting
confidence: 77%
“…It would be interesting to determine whether the latter mutation is also involved in the overproduction of Eap. Glucose was shown to repress SaeS, leading to downregulation of Eap (59); however, MR23 still produced a large amount of Eap even in the presence of glucose (34). Therefore, other factors, apart from SaeS, should also be involved in the extremely large amount of Eap in MR23.…”
Section: Roles Of Eap and Sasg In Biofilm And Pathogenesismentioning
confidence: 99%
“…As observed for many bacteria, during biofilm maturation S. aureus can suffer lysis and release its genomic DNA, producing the so-called external DNA (eDNA), which is a major component of the matrix of biofilms established by this bacterium (Sugimoto et al, 2018). The eDNA adsorbs to the surface of a single cell in long loop structures, which act as an adhesive substance that facilitates cell attachment, in addition to influence the hydrophobicity of the bacterial cell surface (Okshevsky and Meyer, 2015).…”
Section: Biofilms As the Perfect Place For Horizontal Gene Transfer Amentioning
confidence: 99%